How Do Digital Technologies Affect Household Welfare in Developing Countries? Evidence from Senegal - Rodriguez-Castelan, Carlos (World Bank, Washington, DC, 2021)
Developing countries are implementing policies expanding the adoption and productive use of digital technologies to advance economic development and inclusion. Yet, systematic analyses of the welfare and distributional effects of digital technologies on households and individuals—especially broadband mobile internet—remain limited. To fill this knowledge gap, this paper proposes a simple analytical framework to offer insights on how more equitable access to digital technologies affects household welfare, which can be organized into four areas: (1) determinants of adoption of digital technologies; (2) distributional effects of increasing competition in the information and communication technology industry; (3) welfare and poverty effects of coverage and access to digital technologies; and (4) local economic effects of access to digital technologies. To illustrate the relevance and replicability of this framework across developing countries, the analysis is carried out for Senegal, a country that has recently experienced a rapid expansion in digital infrastructure.